Non-Living Creature Personification in Wiz Khalifa Selected Songs - Ni Wayan, Budi Antari; Santika, I Dewa Ayu Devi Maharani (Institut Pariwisata dan Bisnis Internasional, 2024)
Songs as one of literary works often use figurative languange, such as personification. To give human attribute to things, animal or abstarct object will give some varied ways in expressing the feeling or thought. this study aimed to analyse the non-living personification on Selected songs of Wiz Khalifa as well as the meaning. The theory used is the theory of (Zhu, 1991) about Non-Living personification and describe the meaning of the lyrics using the theory of meaninf fom (Leech, 1981). The method that used in this study is qualitative research, where the data is collected by observation and note taking methods. After analyzing the data, the writer concludes in each of selected songs , namely: Sucker of pain, Speed me up, Medicated, Hope less romatic, there are some lyrics tahat contain Non-Living personification based on personidfication Theory by (Zhu, 1991), The result show there are 5 data for non-living personification in the lyrics. The sentence that contained this personification have conceptual, connotative , social and thematic meaning based on the theory of meaning by (leech, 1981).